2015
DOI: 10.1186/s12916-015-0379-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety of serotonin (5-HT3) receptor antagonists in patients undergoing surgery: a systematic review and network meta-analysis

Abstract: BackgroundSerotonin (5-HT3) receptor antagonists are commonly used to decrease nausea and vomiting for surgery patients, but these agents may be harmful. We conducted a systematic review on the comparative safety of 5-HT3 receptor antagonists.MethodsSearches were done in MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials to identify studies comparing 5-HT3 receptor antagonists with each other, placebo, and/or other antiemetic agents for patients undergoing surgical procedures. Screening se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 157 publications
(147 reference statements)
0
22
1
2
Order By: Relevance
“…Therefore, 5-HT 3 R antagonist (tropisetron, ondansetron, emetron, granisetron, dolasetron, ondansetron and palonosetron) Glatzle et al, 2002) and inhibitor of RyRs (azumolene and dantrolene) (Krause et al, 2004) could be used as therapeutic drugs for clinical treatment. Cohort studies further confirmed that particularly ondansetron has fewer side effects in humans up to now (Tricco et al, 2015). In addition, a recent study on poultry would be of interest, which showed that DON reduces the Na + -dependent glucose cotransport and has an effect on Ca 2+ homeostasis (Awad et al, 2014).…”
Section: Deoxynivalenol-induced Vomit In Different Animal Modelsmentioning
confidence: 84%
“…Therefore, 5-HT 3 R antagonist (tropisetron, ondansetron, emetron, granisetron, dolasetron, ondansetron and palonosetron) Glatzle et al, 2002) and inhibitor of RyRs (azumolene and dantrolene) (Krause et al, 2004) could be used as therapeutic drugs for clinical treatment. Cohort studies further confirmed that particularly ondansetron has fewer side effects in humans up to now (Tricco et al, 2015). In addition, a recent study on poultry would be of interest, which showed that DON reduces the Na + -dependent glucose cotransport and has an effect on Ca 2+ homeostasis (Awad et al, 2014).…”
Section: Deoxynivalenol-induced Vomit In Different Animal Modelsmentioning
confidence: 84%
“…Furthermore, it was assumed that the effects of the different doses and durations were identical across the treatments, and that they defined the same node they belong to. We are currently exploring these assumptions in another paper [69]. Although study designs above and beyond RCTs were included, the network meta-analysis was limited to the RCTs in order to increase the confidence of the results.…”
Section: Discussionmentioning
confidence: 99%
“…QT prolongation is a class adverse effect of these agents. In the light of evidence, special attention is warranted for cancer patients with cardiac disease or elderly cancer patients on polypharmacy (48)(49)(50). The NCCN guidelines recommend intravenous palonosetron as the preferred 5-HT3 antagonist (22).…”
Section: -Hydroxytryptamine (5-ht3) Receptor Antagonistsmentioning
confidence: 99%